2016
DOI: 10.1071/fp16120
|View full text |Cite
|
Sign up to set email alerts
|

Potassium fluxes and reactive oxygen species production as potential indicators of salt tolerance in Cucumis sativus

Abstract: Salt stress, among other abiotic stresses, has a high impact on crop yield. Salt tolerance is a multifactorial trait that involves the ability of cells to retain K ions, regulate reactive O species (ROS) production, and synthesise new molecules to cope with osmotic stress. In the present work, two different cultivars of Cucumis sativus L. (cv. Parys, sensitive; cv. Polan, tolerant) were selected based on their germination capabilities under 100 mM NaCl. The capacity of these two cultivars to tolerate salt stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…These pharmacological and genetic results suggest that RBOH-mediated ROS acts as a downstream signal of melatonin to enhance K + retention in rice under salt stress. Consistent with this notion are previous reports that RBOH can improve salt stress tolerance by regulating K + homeostasis in several plant species (Huang et al, 2019;Lockhart, 2013;Ma et al, 2012;Redwan et al, 2016). Thus, melatonin enables initiation of NADPH-mediated transient ROS production without compromising intracellular K + homeostasis.…”
Section: Discussionsupporting
confidence: 83%
“…These pharmacological and genetic results suggest that RBOH-mediated ROS acts as a downstream signal of melatonin to enhance K + retention in rice under salt stress. Consistent with this notion are previous reports that RBOH can improve salt stress tolerance by regulating K + homeostasis in several plant species (Huang et al, 2019;Lockhart, 2013;Ma et al, 2012;Redwan et al, 2016). Thus, melatonin enables initiation of NADPH-mediated transient ROS production without compromising intracellular K + homeostasis.…”
Section: Discussionsupporting
confidence: 83%
“…Salinity stress tolerance in plants is reportedly conferred by K + retention and Na + exclusion from the shoots (Shabala, 2017). Positive correlations between K + retention in plant tissues and salinity tolerance have been reported in wheat (Wu et al, 2015), alfalfa (Guo et al, 2016), cotton (Wang et al, 2016), mustard (Chakraborty et al, 2016), and cucumber (Redwan et al, 2016). Salt tolerant genotypes maintain high K + /Na + ratios under salinity stress; this has been reported by Wu et al, (2015) in barley and by Xiong et al, (2018) in melon.…”
Section: Discussionmentioning
confidence: 97%
“…H 2 O 2 is an early response of K + deficiency and externally added H 2 O 2 was sufficient for the induction of the high-affinity K + uptake (Shin and Schachtman, 2004;Wang et al, 2017). Although there was no report on the correlation between AKT2 and HAK1 regulated K + homoeostasis and H 2 O 2 accumulation in plant drought tolerance, positive relationships between H 2 O 2 production and K + accumulation under salt stress were found for Arabidopsis, cucumber (Cucumis sativus) and pumpkin (Cucurbita moschata) (Huang et al, 2019;Ma et al, 2012;Redwan et al, 2016). For instance, it was demonstrated that higher salt tolerance in pumpkin is related to its higher K + uptake and H 2 O 2 accumulation in the root apex.…”
Section: Hvakt2 and Hvhak1 Modulate Ion Homoeostasis And Signalling Fmentioning
confidence: 99%